Development of a nutritious cereal-based instant porridge by the incorporation of protein-rich insect powder – An example from Zimbabwe - Moira Ledbetter; Jonathon Desmond Wilkin; Juliet Mubaiwa; Faith Angeline Manditsera; Lesley Macheka; Faith Matiza Ruzengwe; Obert Nobert Madimutsa; Prosper Chopera; Tonderayi Mathew Matsungo; Sarah C Cottin; Edryd William Stephens; Viren Ranawana; et al. (Journal of Functional Foods, 2024)
Maize in Zimbabwe lacks essential nutrients like protein, iron, and zinc. This study explored alternative ingredients, including climate smart cereals used in porridge, to address this issue. A fortified porridge was developed by adding mopane worm powder, known for its high protein content. Consumer analysis in the UK and Zimbabwe confirmed acceptability of the fortified porridge. The study also assessed the nutritional quality by examining protein, iron, and zinc bioaccessibility after digestion. Results showed a significant increase in the porridge's nutritional profile. A 20 kg child consuming a 50 g portion of the fortified porridge had a potential 230 % increase in protein uptake and 164 % and 109 % increases in iron and zinc uptake, respectively. Acknowledging dietary diversity and use of local raw materials, the study concludes that food-to-food fortification offers a recommended and sustainable solution to address food security challenges in sub-Saharan African nations.